(untitled) (Devenires, 2021)
The aim of this paper is to evaluate the relation between violence and subjectivity with respect to the problem of vulnerability in the philosophy of Jean Paul Sartre, in the context of the critical turn in phenomenology. In this regard I suggest that violence, understood as a phenomenon of sense, is not explained from a mere instrumental perspective, as a resource among others in order to accomplish practical goals, but as we will observe, violence supposes a distortion of the relation between means and aims in the practical context, based in the inner structure of subjectivity. Thus, in order to explain the difference between violence and counter-violence in Sartre, I turn my attention to the relevance of vulnerability as a source of ethical orientation for the constitution of subjectivities in resistance, in dialogue with Bolívar Echeverría’s account of dialectical violence.